Removal of Synthetic Estrogens in Attached Growth System - Kasmuri, Norhafezah; William Lovitt, Robert; Suja, Fatihah (International Journal of Engineering and Technology, 2019)
Effective treatment of wastewater is crucial to reduce the impact of industry and human activities on the environment. Thus, a more efficient water treatment is needed to remove the components of waste, or the pollutants, faster. Hence in the case of this study, the aim was to investigate the use of bio-filters to remove ammonia-nitrogen and endocrine disrupters (17Î±-ethynylestradiol, the EE2, and mestranol, the MeEE2) in a batch culture experiment. The initial concentrations of 100 Âµg/L of EE2 and 100 Âµg/L of MeEE2 were prepared and added to the batch reactor with bio-filters.Â The bio-filters contained four concentrations of ammonia-nitrogen which were 35 mg/L, 65 mg/L, 85 mg/L and 100 mg/L. The results showed that with 35 mg/L of ammonia-nitrogen, the concentration of the EE2 and the MeEE2 was reduced to 30 Âµg/L showing 70% of them removed over the incubation period.Â Whereas with 65 mg/L of ammonia-nitrogen, the EE2 and MeEE2 were reduced to 27 Âµg/L and 22 Âµg/L, of which 73% of the EE2 was removed while the MeEE2, 78%.Â Thirdly, with 85 mg/L ammonia-nitrogen, the concentration of both oestrogens was reduced nearly the same, which was the EE2 16 Âµg/L and the MeEE2 14 Âµg/L. Here, 84% of the EE2 was removed and the MeEE2, 86%. Lastly, using 100 mg/L of ammonia-nitrogen, the concentrations of the EE2 and the MeEE2 were reduced to 11 Âµg/L and 14 Âµg/L, thus removing 89% of the former and 86% the later. These results displayed the highest removal of oestrogens in comparison with other experiments at different initial concentrations of ammonia-nitrogen in the attached growth system of bio-filters. Â Â